Finding the needle in the haystack [search engines]. - Cass, S.
A new search technology could make peer-to-peer networks easier to use and help them become a legitimate online distribution channel. The decentralized designs common to public peer-to-peer networks make them resistant to legal or technological disruption, but they also create a weakness: it's hard to find anything but the most popular material, usually illegal music or barely legal pornography. Now, Los Angeles-based Streamcast Networks Inc. hopes to fix that weakness and to improve peer-to-peer's image into the bargain with a new search technology known as NEOnet. NEOnet is integrated into Streamcast's signature peer-to-peer software, Morpheus. NEOnet is so important to Streamcast's strategy. It seeks, through NEOnet's improved ability, to find files other than musing or the pinup du jour, to get users to accept Streamcast's peer-to-peer network as a reliable place to find legitimate information, entertainment or software, much as the Web is used today. But NEOnet also offers the advantage that a peer-to-peer network can help share the load currently associated with hosting such content on the Web.
Keywords: Morpheus; NEOnet; Streamcast Networks Inc; Legitimate online distribution channel; Peer-to-peer network; Peer-to-peer software; Search technology